2012
DOI: 10.4012/dmj.2011-177
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Sr-containing carbonate apatite as a bone substitute and its properties

Abstract: Sr-containing carbonate apatite (SrCAp) specimens of varied Sr contents, ranging from 0 to 13.3 mol%, were prepared through a phosphate treatment of set gypsum-and-carbonate mixture at 100°C for 7 days. Effects of Sr content in SrCAp on microstructure, osteoblast-like cell (MC3T3-E1) attachment and proliferation, and alkaline phosphatase (ALP) activity were evaluated. Sr 2+ ion substituted Ca 2+ ion in the apatite lattice. Carbonate content was about 9-13.6 wt%, increasing in content level as Sr content increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Figure 3 shows SEM micrographs of the as-sputtered films of Sr0-Sr100. This result is consistent with the results of other studies [16,28]. After the hydrothermal treatment, the surface morphology was drastically changed (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Figure 3 shows SEM micrographs of the as-sputtered films of Sr0-Sr100. This result is consistent with the results of other studies [16,28]. After the hydrothermal treatment, the surface morphology was drastically changed (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…It has previously been demonstrated that Sr significantly influences osteoblastic differentiation by increasing alkaline phosphatase activity, real-time PCR for ALP and osteocalcin mRNA expression, and alizarin red staining for mineralization. Furthermore, recent investigations have also demonstrated a positive correlation of Sr incorporation into biomaterials [38], [39].…”
Section: Discussionmentioning
confidence: 90%
“…2 It is known, that the process of bone formation is tightly controlled by several systemic and in situ biological agents. Strontium is well known to impart positive effects on human mesenchymal stem cells (hMSC) differentiation, bone formation and remodeling ability in vivo [3][4][5][6][7][8] by a dual effect, namely the decrease of osteoblast activity and the increase of osteoclast activity, 9 constituting the main reasons to be used for treatment of osteoporosis during the last few decades, mainly in the form of complexes with organic acids such as ranelic acid via oral administration. In this regard, a controlled local release of strontium is the most desired administration "route" in order to overcome some of the drawbacks associated with existing methods of systemic administration.…”
Section: Introductionmentioning
confidence: 99%